2015
DOI: 10.4067/s0717-95022015000200043
|View full text |Cite
|
Sign up to set email alerts
|

The Localization of the Asterion According to the Anatomical Landmarks of Posterior Cranial Fossa in Newborns: Clinical Implications

Abstract: SUMMARY:The purpose of this study was to determine the localization of the asterion according to the anatomical landmarks of posterior cranial fossa and its relation with sinuses for posterolateral surgical approaches in newborns. On 70 head-halves, a needle about 2 mm with diameter was placed on the centre point of asterion (posterolateral fontanel) by inserting into the whole cranial bony tissue by forming an right angle with the bony surface. Various localizations of asterion and its measurements from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…7,16 Therefore, the right asterion is more likely to be either directly, or superiorly related to the right transverse-sigmoid sinus junction, in comparison to the left side (Table III). Similar results were reported by Demir and et al (2015), mentioning that their sample consisted of neonatal cadavers aged between 38-40 gestational weeks. 19 This study confirms that variations in the relation of the inion to the confluence of sinuses, as well as the relation of the asterion to the transverse-sigmoid sinus junction, do exist, especially when compared with other studies, as previously reported.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…7,16 Therefore, the right asterion is more likely to be either directly, or superiorly related to the right transverse-sigmoid sinus junction, in comparison to the left side (Table III). Similar results were reported by Demir and et al (2015), mentioning that their sample consisted of neonatal cadavers aged between 38-40 gestational weeks. 19 This study confirms that variations in the relation of the inion to the confluence of sinuses, as well as the relation of the asterion to the transverse-sigmoid sinus junction, do exist, especially when compared with other studies, as previously reported.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were reported by Demir and et al (2015), mentioning that their sample consisted of neonatal cadavers aged between 38-40 gestational weeks. 19 This study confirms that variations in the relation of the inion to the confluence of sinuses, as well as the relation of the asterion to the transverse-sigmoid sinus junction, do exist, especially when compared with other studies, as previously reported. Variations found in the location of the asterion might be ascribed to population-specific locations or sexual dimorphism.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It represents one of the latest surgical frontiers and poses surgical challenges for the otolaryngologists and the neurosurgeons. (1,2) Otologic and neurotologic skull base surgery requires a thorough knowledge of the temporal bone anatomy, as the temporal bone is one of the great gateways of the skull. (3) Its petrous portion gives the passage for the internal carotid artery, vestibulocochlear nerve and facial nerve.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Its petrous portion gives the passage for the internal carotid artery, vestibulocochlear nerve and facial nerve. (4) Therefore, in order to identify and safely approach the vital structures in the skull base during surgeries, many accessible anatomical surface landmarks like the mastoid tip, the digastric muscle, the spine of Henle, the cribriform area, the temporal line, the external auditory canal and the root of the zygomae (2) are used to relate and access the underlying anatomical structures. The Henle's Spine (HS)/spina suprameatica/spina suprameatalis/meatal spine or spina meatus, is a small bony prominence anterior to the supramastoid pit at the posterosuperior margin of the bony external acoustic meatus ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%